Optimalisasi Penerapan Keselamatan dan Kesehatan Kerja (K3) pada Kapal Transhipment Batubara Milik PT. Kartika Samudra Adijya Site Tanah Grogot - Rival Ardi Naga; Dian Junita Arisusanty; Teguh Pribadi (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
In the operation of ships, there are a lot of jobs, both light and heavy, that have a high risk to occupational safety. Work accidents do not only occur on land, but work accidents often occur on ships. The research method used is qualitative, namely data collection through documentation, observation, and interviews with data analysis techniques using Fishbone Diagrams to determine what are the possible obstacles in the implementation of the use of personal protective equipment, factors that cause work accidents in the crew, and efforts made to optimize the implementation of occupational safety and health on board and determine the priority of problems. By using Fishbone Diagram as a data analysis technique, the root cause of the problem can be found. Based on these data analysis techniques, the causes of work accidents on ships often occur due to lack of awareness, low supervision, and lack of understanding of the crew at work. In addition, there are also other factors, namely work equipment that is not suitable for use. Work accidents can be prevented if the company's leadership and all executives are committed to developing and implementing effective occupational safety and health procedures. This includes instilling awareness of the importance of work safety, direct guidance and supervision to the crew of ships, as well as the establishment of a safety management system supported by skilled human resources and adequate safety equipment facilities. The implementation of optimal K3 procedures will create a safe and efficient work environment, so that ship operations can run smoothly and work accidents can be prevented.